A Study on Contribution of Wireless Networks in Enhancement of Security: Exploring the Role of Wireless Networks in Improving Security and User Awareness (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Wireless networks security joined with new security dangers and changes the affiliation's general data security hazard profile. System in security has turned into an expanding problem in the world of PC networks. Technical experts have attempted to battle this by improving the technical consciousness of the threats and technical arrangements engaged with Wireless Local Networks (WLAN) through technical reports and policy implementation. The normal users' knowledge and consciousness of system security, how they respond to the warnings and actualize security measures is additionally significant. Current examinations on users' consciousness of security policies, regardless of whether it has been conveyed all around ok and how mindful WLAN users are to the threats and issues included are as yet not completely found out. A security exploit is a readied application that exploits a known weakness. we need to instruct individuals and associations on the most proficient method to optimal use safety highlights.